South Asia’s exports to the EEC : - Cable, Vincent (Overseas Development Institute, 1979)
The research presented in this book would not have been possible without the encouragement, assistance, guidance, and support of many people. Historical and institutional background, the economic basis of EEC-South Asia Relation; Tariffs, references and South Asia,...